Evaluating laboratory performance on analysis of mandatory nutrients for nutrition labelling - Boonpor, Jirapitcha; Judprasong, Kunchit; Puwastien, Prapasri (Asia-Pacific Journal of Science and Technology, 2017)
Reliable nutrient composition data on a food label is important information to assist the consumers in making the right choice for healthy processed foods. Previous studies on nutrition labelling indicated considerable problems of non-complied information based on the Thai Food and Drug Administration (Thai FDA) regulations. The main issue involving the unreliable nutrient information could be the laboratories who take responsibility for developing the nutrient composition data. This study aimed to investigate the performance of laboratories on analysis of mandatory nutrients, and the preparation of nutrition labelling. For laboratory performance, whole wheat cracker and cracker powder were used as test materials. Participating laboratories (16 laboratories) were requested to analyse mandatory nutrients for nutrition labelling and to use the obtained data to prepare ready-to-use nutrition information based on the Thai FDA regulations. Laboratory analytical performance was statistically evaluated using z-score. For whole wheat cracker, good laboratory performance (|z-score| < 2) was found satisfactory performance on analyses of total fat, protein, sodium, moisture, and ash. Moreover, cracker powder was found on the analyses of those nutrients as well as the analyses of saturated fat, dietary fibre, calcium, and iron. Unsatisfactory performance was found on analyses of vitamin B1 and B2 and sugars. The findings strongly demonstrate good performance of laboratory for mandatory nutrients which could provide reliability of the nutrition information on food labels.